The Correlation Between Falls and Cognitive Frailty in Elderly Individuals With Hypertension in a Chinese Community - Wang, Can; Chong, Yue; Wang, Ling; Wang, Yanbo (Frontiers in Aging Neuroscience, 2022)
Background: Cognitive frailty refers to the presence of both physical frailty and mild cognitive impairment without simultaneous diagnosis of Alzheimer's disease or other dementia. Epidemiological studies have confirmed the correlation between falls and cognitive frailty, but no study has investigated the relationship between fall risk and cognitive frailty in hypertensive elderly Chinese individuals. Methods: From December 2020 to March 2021, during face-to-face interviews, community-dwelling elderly individuals with hypertension aged 60~89 in Pudong New Area, Shanghai, were evaluated for cognitive frailty, fall history, and depression, and sociodemographic characteristics were collected. Logistic regression was used to analyze the correlation between falls and cognitive frailty. Results: A total of 305 elderly people were investigated in this study, and 173 (56.7%, 95% CI =51.2%~62.2%) reported falling once or more in the previous year. Cognitive frailty is closely related to falls and was an independent risk factor for falls (OR = 2.661, 95% CI = 1.063~6.659). Other risk factors included old age (OR = 4.306, 95% CI = 1.852~10.013), female sex (OR = 1.988, 95% CI = 1.185~3.335) and depression (OR = 2.936, 95% CI = 1.069~8.060). Conclusion: Cognitive frailty is an important risk factor for falls in elderly individuals with hypertension in Chinese communities.